Proactive Risk Assessment Through Failure Mode and Effect Analysis (FMEA) for Haemodialysis Facilities: A Pilot Project - La Russa, Raffaele; Fazio, Valentina; Ferrara, Michela; Di Fazio, Nicola; Viola, Rocco Valerio; Piras, Gianluca; Ciano, Giuseppe; Micheletta, Fausta; Frati, Paola (Frontiers in Public Health, 2022)
Haemodialysis (HD) is one of the methods for renal replacement therapy in the management of advanced chronic kidney disease through an osmosis process that allows purification of blood in the dialysis machine. The complexity of the dialytic procedure often requires the presence of a multi-specialist, multi-disciplinary team. The dialysis process is an important target for clinical risk management. Failure Mode and Effect Analysis (FMEA) is a proactive technique, considered a purposeful and dynamic tool for clinical risk management. FMEA is noted in five phases that allow a preliminary assessment of a definite process through identification and classification of risk priorities. This study represents the first of a two-phase project where FMEA is applied to HD in the setting of San Feliciano Hospital. The dialysis center performs ~12,000 dialysis sessions per year. The dialysis process is divided into different stages. A total of 31 failure modes were identified in the whole dialysis stages; more than 2/3 of the failure modes were related to the only connecting of the patient to the dialysis machine. The first phase of the study clearly remarked that the most critical step of the dialytic process is represented by the connection between the patient and the machine, as expected. Indeed, in order to have the dialysis set up, an arteriovenous fistula must be surgically created prior to the procedure and it is one of the most important issues in the HD process because of the necessity of a constant revision of it. FMEA application to HD is a useful tool, easy to be implemented and it is likely to nimbly reveal the practical and potential solutions to the critical steps of the procedure.